The warrior heir eaudiobook - Chima, Cinda Williams (Heir Chronicles, 2006)
A teen from Ohio discovers he's the last in a long line of magical warriors chosen to fight to the death. Before he knew about the Roses, sixteen-year-old Jack lived an unremarkable life in the small town of Trinity, Ohio. Only the medicine he has to take daily and the thick scar above his heart set him apart from the other high-schoolers. Then one day Jack skips his medicine. Suddenly, he is stronger, fiercer, and more confident than ever before. And it feels great—until he loses control and nearly kills another player during soccer team tryouts. Soon, Jack learns the startling truth about himself: He is Weirlind, part of an underground society of magical people living among us. At the head of this magical society sit the feuding houses of the Red Rose and the White Rose, whose power is determined by playing The Game: a magical tournament in which each house sponsors a warrior to fight to the death. As if his bizarre magical heritage wasn't enough, Jack finds out that he's not just another member of Weirlind—he's one of the last of the warriors, at a time when both houses are scouting for a player. Can he learn to control his magic and fight off the Wizards who would claim him? Find out in the first book in the epic Heir Chronicles series by New York Times and USA Today bestselling author Cinda Williams Chima!